Vital functions of the malarial ookinete protein, CTRP, reside in the A domains. - Ramakrishnan, C; Dessens, J; Armson, R; Pinto, S; Talman, A; Blagborough, A; Sinden, R (2011)
The transformation of malaria ookinetes into oocysts occurs in the mosquito midgut and is a major bottleneck for parasite transmission. The secreted ookinete surface protein, circumsporozoite- and thrombospondin-related adhesive protein (TRAP)-related protein (CTRP), is essential for this transition and hence constitutes a potential target for malaria transmission blockade. CTRP is a modular multidomain protein containing six tandem von Willebrand factor A-like (A) domains and seven tandem thrombospondin type I repeat-like (TS) domains. Here we present, to our knowledge, the first structure-function analysis of CTRP using genetically modified Plasmodium berghei parasites expressing mutant versions of the ctrp gene. Our data show that the A domains of CTRP are critical for ookinete gliding motility and oocyst formation whilst, unexpectedly, its TS domains are fully redundant. These results may have important implications for the design of CTRP-based transmission blocking strategies.